Sistem Informasi Monitoring Nilai Siswa Berbasis Website - Romi Julio; Ade Pratama; Ami Anggraini Samudra (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This research was conducted to create a website-based student grade monitoring information system, where the process of scoring was carried out by the teacher writing students' scores directly into a grade recap book or folio paper with information on dates, student names, subjects, and the grades achieved. This system is done by designing, making, and implementing. The model used in this research is SDLC (System Development Life Cycle). In making this website in order to control the stages of work carried out by system analysis in building information systems. For testing this system is done using the Blackbox test. The results obtained from this study can make it easier for teachers in the process of value input, both in the form of daily practice scores, notes, daily tests, uts, uas and can make it easier for parents to monitor their children's activities in school. With this system, it is hoped that it can be useful for teachers in inputting values and can be useful for parents in monitoring the value activities of their children at school. Keywords: System, Value, SDLC, Monitoring